THU0028 Interleukin-6 receptor inhibition, as first-line b-dmard, affects b cell subpopulations distribution through epigenetic modifications in rheumatoid arthritispatients. (12th June 2018) - Alivernini, S.; Tolusso, B.; Fedele, A.L.; Di Mario, C.; Petricca, L.; Di Sante, G.; Gigante, M.R.; Ferraccioli, G.; Gremese, E.
Abstract : Background: Despite IL-6R inhibition was found to influence B cell subpopulations distribution in Rheumatoid Arthritis (RA), no data are available on the effect on epigenetic signature of RA B cells by this treatment. It is well known that B cell maturation is under control of the microRNA-155 (miR-155)/PU.1 axis significantly influenced by IL-6 stimulation 1 . Objectives: To investigate the effect of IL-6R inhibition on the epigenetic signature of B cells (miR-155/PU.1 axis) in RA patients. Methods: Twenty-nine RA patients [18 (62.1%) female; 57.2±14.9 years old; disease duration 1.3±0.7 years] starting IL-6R inhibitor treatment as first b-DMARD, have been enrolled. At study entry and after 3–6–12–18 months follow-up, CD19 + cells were isolated from peripheral blood (PB) by magnetic microbeads (Miltenyi) and B cells subpopulations were assessed through FACS according to the IgD/CD27 classification. MiR-155 and PU.1 endogenous expression was determined in PB-derived CD19 + cells by RT-PCR at baseline and after 3–6–12–18 months follow-up. IL-6 plasma level was assessed by ELISA at study entry for each patient. ACR/EULAR criteria were used to assess the response rate to IL-6R inhibitor treatment for each RA patient. PB-derived CD19 + cells of healthy individuals (HC) were used as comparison group. Results: At study entry, RA patients showed higher percentage of IgD - /CD27 - CD19 + cells (p<0.05) and IgD + /CD27 + CD19 + cells (p<0.05) than HC. Moreover, IgD - /CD27 - CD19 + cells percentage directly correlated with Disease Activity Score (p=0.04) and IL-6 plasma levels (p=0.06) in RA patients. IL-6R inhibition lead to DAS and SDAI remission achievement in 73.9% and 52.2% of RA patients after 18 months follow-up, respectively, and significantly reduced IgD - /CD27 - CD19 + cells percentage after 18 months follow-up (p<0.02). Stratifying RA patients based on the remission achievement during the follow-up, RA patients who achieved DAS remission under IL-6R inhibition showed a significant decreased of IgD - /CD27 - CD19 + cells percentage compared to patients not achieving this outcome (p<0.05), reaching IgD - /CD27 - CD19 + cells percentage comparable to HC (p>0.05). Analysing the epigenetic profile in B cells of RA patients, at baseline, PB-derived CD19 + cells of RA patients showed significantly higher endogenous expression of miR-155 (p=0.04) than HC. Moreover, RT-PCR showed that IL-6R inhibition significantly represses endogenous miR-155 expression in PB-derived RA B cells already after 3 months of treatment (p<0.05) and restores PU.1 expression in PB-derived B cells after 6 months (p<0.05) only in RA patients achieving disease remission. Conclusions: IL-6R inhibitor, used as first b-DMARD treatment, acts restoring B cells homeostasis through epigenetic modulation in RA. In particular, IL6-R inhibition significantly represses endogenous expression of miR-155 in PB-derived CD19 + cells conversely restoring PU.1 expression mirrored by the decrease of IgD - /CD27 - B cell rate in RA patients achieving disease remission. Reference: [1] Alivernini S, Kurowska-Stolarska M, Tolusso B, et al. Nat Commun2016. Disclosure of Interest: None declared